Participatory diagnosis of food systems fragility; perspectives from Thailand - Friend, Richard M.; Thiengburanathum, Pongtip; Harrison, Laura J.; Thiengburanathum, Poon; Doherty, Bob; Thankappan, Samarthia (Frontiers in Sustainable Food Systems, 2023)
Much of the effort has been directed at identifying appropriate metrics and indicators of system resilience, and from this, interventions to strengthen resilience. An essential ingredient of such resilience-building efforts is to apply public processes of dialogue and diagnosis to identify systems fragility and potential for failure. Social learning processes allow people to take new perspectives in understanding their own and other’s interests and values and to more clearly formulate problems and identify the potential for systemic failure. Diagnosis and dialogue tools used in a participatory process in Northern Thailand included food systems mapping, identifying potential points of failure, and applying a self-assessment tool structured around resilience characteristics. This process proved important for developing stakeholder understanding of systems thinking and of concepts of resilience. Yet it is a process that is not without challenges. We noted the difficulty with defining food system boundaries and the tendency for participants to persist with familiar understandings of problems within their sector, with it taking time to shift to thinking about points of fragility within the whole system. We particularly recognize the participatory process itself as being of value, in addition to the specific outcomes such as risk identification or interventions for resilience.